2012
DOI: 10.4236/jct.2012.325084
|View full text |Cite
|
Sign up to set email alerts
|

p53 Expression in Triple Negative Breast Carcinomas: Evidence of Age-Related and Racial Differences

Abstract: Triple negative breast carcinomas (TNBC), are defined by the absence of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) expression. The majority of TNBC are "basal-like", a group originally defined by studies of mRNA gene expression profiles, but increasingly defined in the clinic by using surrogate markers such as CK 5/6. However, not all TNBC are basal-like. It is postulated that these subcategories of TNBC have distinct underlying biologies that drive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The relationship between the expression of ER and PR, ER and HER2/neu, PR and HER2/neu, p53 and Ki-67, ER and Ki-67, PR and Ki-67 indicate the presence of close cooperation between the various links of IDC progression [ 10 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the expression of ER and PR, ER and HER2/neu, PR and HER2/neu, p53 and Ki-67, ER and Ki-67, PR and Ki-67 indicate the presence of close cooperation between the various links of IDC progression [ 10 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be used for stratification of this heterogeneous subtype of breast cancers into subgroups according to prognosis and chemotherapeutic response (34). It was shown that p53 positivity in TNBC correlates with poor survival, worse response to therapy and is more common in younger patients (35, 36). Our study could not corroborate the usefulness of p53 expression as a prognostic biomarker for OS in TNBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, we suggest that there may be dysregulation up or downstream of these pathways as a result of a mutation, and the increase in activity of these pathways could be explained by the patient’s cells attempting to compensate for dysregulation. p53-expressing tumors are more frequent in AA women with TNBC when compared to their CA counterparts with TNBC [ 58 ], so the increase in expression of the p53 subnetwork could be partially explained by this fact.…”
Section: Discussionmentioning
confidence: 99%